2018
DOI: 10.1037/ipp0000080
|View full text |Cite
|
Sign up to set email alerts
|

The Headington Institute Resilience Inventory (HIRI): Development and Validation for Humanitarian Aid Workers

Abstract: We developed the Headington Institute Resilience Inventory as a psychometrically valid, multifactored self-report measure to identify dimensions of resilience for international aid workers. We define resilience as the capacity to adapt during traumatic incidents so that one not only just survives but survives well. By utilizing a dynamic approach to resilience to predict this adaptive capacity, we aim to identify dimensions that could lead to personalized protective training exercises, essential because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Resilience is thus an adaptive and interactive construct, wherein, by intervening, a person can decrease or increase his or her personal resilience (Herrman et al, 2011). The Headington Institute, an organization that supports aid workers through research and hands-on care, has identified seven individual factors that contribute to resilience: adaptive engagement, spirituality, emotional regulation and cognitive clarity, behavioral regulation, physical fitness, sense of purpose, and life satisfaction (Nolty et al, 2018).…”
Section: Humanitarian Aid Workers and Stressmentioning
confidence: 99%
“…Resilience is thus an adaptive and interactive construct, wherein, by intervening, a person can decrease or increase his or her personal resilience (Herrman et al, 2011). The Headington Institute, an organization that supports aid workers through research and hands-on care, has identified seven individual factors that contribute to resilience: adaptive engagement, spirituality, emotional regulation and cognitive clarity, behavioral regulation, physical fitness, sense of purpose, and life satisfaction (Nolty et al, 2018).…”
Section: Humanitarian Aid Workers and Stressmentioning
confidence: 99%
“…The Antares Foundation (2012) published a practical manual for Managing Stress in Humanitarian Workers . The Headington Institute focuses more narrowly on the concept of resilience as a critical trait for aid workers and built a self-reporting resilience scale based on seven elements: adaptive engagement, spirituality, emotional regulation, behavioural regulation, physical fitness, sense of purpose, and life satisfaction (Nolty et al, 2018).…”
Section: Work–life Intersections In Peacebuilding Development and Humanitarian Aidmentioning
confidence: 99%
“…Described as a catastrophe, a conflict, or a confrontation, this is an event that disrupts the normal progression of a person's life, resulting to a possible activation of one's resilience mechanisms (Chmitorz et al, 2018). After this disruption, resilience is a pathway to adaptation, identified as the ability to safeguard one's psychological stability and to progress in life (Nolty, Bosch, An, Clements & Buckwalter, 2018), as well as to eschew maladaptive ways of dealing, such as alcohol or drug misuse or some form of delinquency (Rudzinski, McDonough, Gartner & Strike, 2017). Linked to acute life disruptions, resilience has been shown to develop most in a milieu either of limited challenging occurrences or of ongoing struggles such as in countries that have been war zones for years on end (Liu et al, 2017).…”
Section: People: International Journal Of Social Sciences Issn 2454-5899mentioning
confidence: 99%
“…Factors that favor the maturation of a resilient individual have been described as multifaceted and oscillating from corporal attributes such as physical robustness, to calm psychological reactions, a composed behavior, a sense of appreciation for life, a belief in god or higher powers to a feeling of determination and of ambition (Nolty et al, 2018). In like manner, a person's locus of control which can be described as their understanding of the forces that determine their life can also affect resilience.…”
Section: People: International Journal Of Social Sciences Issn 2454-5899mentioning
confidence: 99%